Processing and Characterization of Magnetron Sputtered Ni/Ti Thin Film and their Annealing Behaviour to Induce Shape Memory Effect - Behera A.; Aich S.; Behera A.; Sahu A. (My University, 2025)
This paper describes the fabrication processes and the novel characterization techniques of the as-deposited as well as the annealed thin films. Deposition of single-bi-layer Ni-Ti thin film on Si(100) substrate have done using DC and RF magnetron sputtering technique. The as-deposited thin films are amorphous in nature, which is annealed at different temperature (300. °C, 400. °C, 500. °C and 600. °C) to induce the crystalline structure. Microstructures were analysed using Field Emission Scanning Electron Microscopy (FESEM) and High-resolution transmission electron microscopy (HRTEM). Atomic force microscopy (AFM) was carried out to know about the mechanical properties and surface profiles of the films. Phase analyses, performed by Grazing incidence x-ray diffraction (GIXRD). It was observed that, for the annealing temperatures varied from 300. °C to 600. °C, the increase in annealing temperature resulted in a gradual increase in atomic-cluster coarsening with improved ad-atom mobility. Phase analyses show the presence of silicide phases and intermetallic compounds. HRTEM reveals the band like structure on the annealed thin film surface which indicated the formation of shape memory alloy. © 2015 Elsevier Ltd.